The Comparison of Masticatory Efficiency between Conventional Complete Denture and Implant Retained Overdenture - Shafqat Hussain, Abdullah, Malak Qaiser, Aamna Mansur, Khuda-E-Dad, Nasir Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The study aimed to compare the masticatory efficiency of conventional complete dentures (CCD) and mandibular implant retained overdentures (IRO). Material and Methods: A quasi experimental study was conducted involving 20 completely edentulous patients divided into two equal groups: Group A received CCD and Group B received implant retained overdentures in the mandibles. Subjective evaluation was carried out which include color change scores on 1-5 likert scale for masticatory efficiency and VAS for chewing satisfaction. Data were analyzed using SPSS 23.0 version and Mann Whitney U test and Spearman’s rank correlation was used to compare performance and examine relationships between variables and level of significance was p<0.05. Results: Subjective color change and VAS rating were also markedly better in IRO group (4.5±0.53 and 8.4±0.70 respectively) than in CCD group (2.7±0.67 and 4.8±0.79; p<0.001). Spearman’s correlation revealed a strong positive relationship between subjective color change score and VAS which were statistically significant (Spearman’s p=0.982, p<0.000001). Conclusion: The findings of this study concluded that implant retained overdentures significantly improve masticatory efficiency and patient satisfaction compared to conventional complete dentures. Keywords: Edentulism, chewing gum, implant-retained overdenture, masticatory efficiency, conventional denture.